2022
DOI: 10.1038/s41598-022-10083-5
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of the postbiotic deriving from cow’s milk fermentation with L. paracasei CBA L74 against Rotavirus infection in human enterocytes

Abstract: Rotavirus (RV) is the leading cause of acute gastroenteritis-associated mortality in early childhood. Emerging clinical evidence suggest the efficacy of the postbiotic approach based on cow’s milk fermentation with the probiotic Lacticaseibacillus paracasei CBAL74 (FM-CBAL74) in preventing pediatric acute gastroenteritis, but the mechanisms of action are still poorly characterized. We evaluated the protective action of FM-CBAL74 in an in vitro model of RV infection in human enterocytes. The number of infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Considering effects of a heat-inactivated L. paracasei CBA L74 for preventing acute gastroenteritis, further studies were conducted to better understand the underlying mechanisms. A 2022 study [10] found, in an in-vitro model of rotavirus infection in human enterocytes, that heat-inactivated L. paracasei CBA L74 positively modulates a range of nonimmune and immune defense mechanisms against rotavirus infection in human enterocytes. Overall, it contributed to the inhibition of the inflammatory status by reducing the generation of proinflammatory markers such as rotavirus-induced reactive oxygen species (ROS) as well as interleukin (IL)-8, IL-6 and tumour necrosis factor (TNF)-α production.…”
Section: Postbiotics In Infants and Childrenmentioning
confidence: 99%
“…Considering effects of a heat-inactivated L. paracasei CBA L74 for preventing acute gastroenteritis, further studies were conducted to better understand the underlying mechanisms. A 2022 study [10] found, in an in-vitro model of rotavirus infection in human enterocytes, that heat-inactivated L. paracasei CBA L74 positively modulates a range of nonimmune and immune defense mechanisms against rotavirus infection in human enterocytes. Overall, it contributed to the inhibition of the inflammatory status by reducing the generation of proinflammatory markers such as rotavirus-induced reactive oxygen species (ROS) as well as interleukin (IL)-8, IL-6 and tumour necrosis factor (TNF)-α production.…”
Section: Postbiotics In Infants and Childrenmentioning
confidence: 99%
“…The fermentation product is then pasteurized at 85 °C for 20 s for the inactivation of the living bacteria, and then spray dried. Thus, the final fermented milk powder contains only bacterial bodies and fermentation products, but not living microorganisms [ 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: The Postbiotic Derived From Cow Milk Fermentation With the P...mentioning
confidence: 99%
“…Intestinal epithelial cells employ a range of defense strategies to counteract RV invasion, including mucus production and cytokines/chemokines expression [ 18 ]. The potential protective action elicited by FM-CBAL74 against RV infection has been recently investigated in a validated model of human enterocytes [ 12 ]. It has been demonstrated that FM-CBAL74 was able to protect against gut barrier damage, characterized by cytoskeleton alterations and apoptosis, involving the ERK/JNK kinase pathway.…”
Section: Preclinical Evidence On the Fm-cbal74 Effects Against Intest...mentioning
confidence: 99%
See 2 more Smart Citations